Climate Change the Global Phenomena, Uganda in Perspective: What is it? What does Policy Makers need to know and to do? - Uganda Wildlife Society (Uganda Wildlife Society, 2011)
Ordinarily, any change in global temperature and rainfall over a period of time. Commonly associated with global warming, the sustained spatio-temporal differential increases in average temperature of earth near surface air and oceans since the 20th century. In practice, radiations from the sun upon reflection from the earth or ocean surface to the atmosphere are reflected back by a layer of green house gasses in the stratosphere. Green house gasses such as Carbon dioxide, Methane, Chlorofloro carbons and Nitrogen oxide come from automobile emissions, bush and charcoal burning, refrigerators and other human activities. The concentration of these green house gasses in the atmosphere, which is the problem, has been increasing among others due to diminishing forest cover in land uses.